Factors affecting the work ability of nursing personnel with post-COVID infection - Warunee Tangsathajaroenporn; Jinjuta Panumasvivat; Kampanat Wangsan; Supang Muangkaew; Wuttipat Kiratipaisarl (Scientific Reports)
Abstract Post-COVID infection have raised concerns regarding their impact on nursing personnel’s work ability. This study aimed to assess the relationship between post-COVID infection and work ability among nursing personnel. A retrospective observational study from December 2022 to January 2023 involved 609 nursing personnel with a history of COVID-19 infection at a tertiary hospital. An online questionnaire measured post-COVID infection, personal and working factors, and the Work Ability Index (WAI). Long COVID was defined as the continuation or development of new symptoms 1 month post COVID-19 infection. Of 609 personnel, 586 showed post-COVID symptoms (fatigue, cough, difficulty breathing, etc.), with 73.72% in the short COVID group and 26.28% in the long COVID group. A significant association was found between WAI and post-COVID infection (aOR: 3.64, 95% CI 1.59–8.30), with the short COVID group had a significantly higher WAI than the long COVID group (mean difference 2.25, 95% CI 1.44–3.05). The factors related to work ability in the long COVID group were chronic diseases, work limitation, low job control (P < 0.05). Post-COVID infection, especially long COVID, adversely affect nursing personnel's work ability. Enhancing job control and addressing work limitations are crucial for supporting their return to work.